NEW LIGHT ON THE SPREAD OF LEPROSY - Rees, R.J.W. (SCHOOL SCIENCE, 2013)
Research in the last few years indicates that, contrary to popular belief, leprosy is most readily transmitted through the nose, where it forms a seat of infection long before other symptoms have become noticeable. The correct explanation was postulated by 19th century doctors in clearly documented observations, which apparently no one followed up.